Sociological theory, modern culture and emancipation: An inconclusive exercise self-clarifying sociological - Dockendorff, Cecilia (MAD, 2007)
<!–[if gte mso 9]> Normal 0 21 false false false ES-TRAD X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>The present article presents the characteristics of the sociological observation around modernity and its relation with the culture. The author concludes that a sociological observation of the culture is necessary for a theory of modernity and the social intervention.